Insurance for Farmer Protection: Indonesian Experience - Candradijaya, Ade (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Agricultural sector is one of the most vulnerable business with high degree of uncertanties. Those sources of risks come from environment such as climate change, natural disaster, endemic pests, and also social economic change affected by international trade conflict. In order to mitigate the above mentioned risks, farmers opt to choose several strategies: (1) to diverse crops production (2) to modify ways of post harvest handling and pocessing in marketing their products, (3) to finance their cultivation by accessing financial institutions and last but not least (4) by protecting their business using agricultural insurance. Majority of smallholder farmers in Indonesia are un-tabbed group who are still lacking their knowledge about insurance. Compared with that of other countries, Indonesia should provide the minimum subsidies of agricultural insurance approximately 40% of the total investment (USA covers 25% of farming total loss, Brasil 50%, Mexico 80%).This paper shares some insight on Indonesian agricultural insurance, its best practice and future recommendation for better policy decision-making. Agricultural insurance in Indonesia has been initated since 2012 through pilot testing in two main commodites, namely paddy insurance (AUTP) and cattle insurance (AUTP). This initiave has been growing well. Further, Ministry of Agriculture formulated road-map of agricultural insurance for the year 2015-2019, with a set target of coverage for AUTP 1 (one) million ha and for AUTS 120.000 heads of cattle per year starting form 2016; and a period of insurance and total premium of 4 months and IDR 180.000; and 1 year and IDR 200.000 for rice and cattle, respectively. The realization of this target has been consistently increasing from 23.30% in 2015 to 50.00% in 2016 and 51.14% in 2017, and at the same time its coverage areas ha also been widened.